KEBERLANJUTAN MATA PENCARIAN NELAYAN SKALA KECIL DI LINGKUNGAN ESTUARI DESA PAGATAN BESAR - Yuni Helda Helda; Anang Kadarsah; Krisdianto Krisdianto (Universitas Lambung Mangkurat, 2023)
Estuary waterscapes, as a combination of freshwater and marine ecosystems, play an important role in ecology and human sustainability. Estuaries play a vital role in maintaining water quality and the fertility of the surrounding land. The social aspect of an estuary waterscape includes community interaction with the ecosystem, where the culture and social growth of coastal communities grows. Various previous studies have identified the environmental and economic impacts of estuary use on fishermen. However, the aspect that remains a question is how the environmental and economic impacts are related to social aspects in the context of fishermen's lives. We will analyze the interaction of various factors to answer how fishermen contribute to getting a decent life for fishing groups with small boats, thus clarifying previously unknown aspects. This research aims to explore information on how to manage and the amount of trash fish waste disposed of in the estuary landscape in Pagatan Besar Village and identify the condition of the quality of the estuary waters in Pagatan Besar Village. Data was collected through surveys of fishermen to find out various fishing tools and techniques, as well as collecting economic and social data through questionnaires and structured interviews. Analysis of environmental, economic and social data is carried out to predict catches, income and sustainability of fishermen's businesses. The results conclude that business sustainability has the potential to support a decent life for groups of fishermen with small boats who utilize the estuarine waterscape.